Análisis crítico de la evolución del juicio de amparo en un contexto de fragmentación moral y pluralismo: Políticas públicas judiciales, restitución y el principio de relatividad. - Estévez Cortes, Alejandro (My University, 2022)
This thesis critically examines the traditional rule for the diplomatic protection of corporations in international law, as established by the International Court of Justice in the Barcelona Traction case, which designates the state of incorporation as the basis for nationality. The author argues that this formalistic criterion is insufficient and often leads to inequitable outcomes, leaving the actual investors—shareholders of a different nationality—without protection. As a more just and realistic alternative, the thesis advocates for the adoption of the "effective control" or "genuine link" principle, which focuses on the nationality of the shareholders who ultimately control the corporation. The analysis traces the evolution of the doctrine, critiques the limitations of the International Law Commission's Draft Articles on Diplomatic Protection, and highlights the widespread adoption of shareholder-based criteria in modern Bilateral Investment Treaties (BITs). The work concludes that the proliferation of BITs demonstrates a clear trend away from the rigid Barcelona Traction precedent and supports the argument that "effective control" should be recognized as the prevailing standard to ensure genuine and effective protection for foreign direct investment.
CAPÍTULO I. HISTORIA Y NATURALEZA DEL JUICIO DE AMPARO -- CAPÍTULO II. ALCANCES DE LA SENTENCIA CONSTITUCIONAL: REPARACIÓN INTEGRAL DEL DAÑO EN EL JUICIO DE AMPARO -- CAPÍTULO III. POLÍTICAS PÚBLICAS JUDICIALES Y EL JUICIO DE AMPARO.
Keywords: Derecho - Tesis